2005
DOI: 10.1509/jmkg.69.3.19.66363
|View full text |Cite
|
Sign up to set email alerts
|

The Social Influence of Brand Community: Evidence from European Car Clubs

Abstract: The authors develop and estimate a conceptual model of how different aspects of customers’ relationships with the brand community influence their intentions and behaviors. The authors describe how identification with the brand community leads to positive consequences, such as greater community engagement, and negative consequences, such as normative community pressure and (ultimately) reactance. They examine the moderating effects of customers’ brand knowledge and the brand community's size and test their hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
1,838
9
81

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,905 publications
(2,000 citation statements)
references
References 39 publications
72
1,838
9
81
Order By: Relevance
“…This was particularly the case, where they had a higher degree of involvement in a product category. Similar findings have been reported in Algesheimer et al 14 who found that the strength of consumers' relationship with a brand community determines the level of community engagement in ''helping other members, participating in joint activities, and otherwise acting volitionally in ways that the community endorses and that enhance its value for themselves and others'' (p. 21).…”
Section: Outcome Of Online Gossipsupporting
confidence: 83%
“…This was particularly the case, where they had a higher degree of involvement in a product category. Similar findings have been reported in Algesheimer et al 14 who found that the strength of consumers' relationship with a brand community determines the level of community engagement in ''helping other members, participating in joint activities, and otherwise acting volitionally in ways that the community endorses and that enhance its value for themselves and others'' (p. 21).…”
Section: Outcome Of Online Gossipsupporting
confidence: 83%
“…Afterwards, lot of marketing scholars have identified various ways to analyze the process of online brand communities advancement such as McAlexander et al, (2002) examined the relationship between consumer participation and brand loyalty, Bagozzi and Dholakia (2006) investigated consumer participation in OBCs, and Tsai et al, (2012) explored the OBCs effects on brand equity through exchange process. The contribution of community participation provides brand manager with relevant information about many product attributes that will guide in product development and improvement (Algesheimer et al, 2005). The long-term success of brand community depends on the participation of existing members and components of community that engage new members.…”
Section: Characteristics Of Online Brand Community (Obc)mentioning
confidence: 99%
“…The highly devoted consumers are best source for product development, co-creation and grassroots marketing campaigns. Thirdly, brand communities are vital for promoting consumer-brand and consumer-consumer relationship because participating in a community creates connection that leads to brand advocates (Algesheimer et al, 2005;Andersen, 2005;Bagozzi & Dholakia, 2006). The brand advocates are consumers that defend the brand and its marketing strategies towards targeted customers.…”
Section: Characteristics Of Online Brand Community (Obc)mentioning
confidence: 99%
“…This takes into consideration the emotional attachment the consumers feel for the brand (see, for instance, Atkin 2004;Cova and Cova 2002;Lindstrom 2005;and Aaker 1997, among others). This emotional attachment also manifests itself in a sense of belonging to a particular brand community (Algesheimer, Dholakia, and Hermann 2005;Cova and Cova 2002). This community generates its own interpretation of the brand and these should relate to the brand values espoused by the brand owners themselves.…”
Section: Brandingmentioning
confidence: 99%